2009
DOI: 10.1007/s00795-009-0464-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression of claudin-4 and -7 in porcine gingival junctional epithelium

Abstract: Junctional epithelium, a nonkeratinized stratified epithelium, extends apically in apposition to the surface of the enamel to form a seal between the epithelium and the tooth. Desmosomes and gap junctions adhere to the junctional epithelium through cell-cell contact, but no evidence of tight junctions has been found. Recently, tight junction hallmark proteins and tight junction-related structures have been identified in stratified squamous epithelium. The present study examined whether tight junction proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Therefore, tight junctions do not appear to contribute to barrier function in the junctional epithelium [11] . Although we reported that claudins exist in the junctional epithelium of rat or porcine gingiva [12] , [13] , their roles in the junctional epithelium have not been elucidated. Furthermore, microarray and immunohistochemical analyses demonstrated that the expression of claudin-1 in the junctional epithelium following a chronic lipopolysaccharide (LPS) challenge was weaker than that in healthy subjects [14] .…”
Section: Molecular Factors Associated With the Function Of The Junctimentioning
confidence: 90%
“…Therefore, tight junctions do not appear to contribute to barrier function in the junctional epithelium [11] . Although we reported that claudins exist in the junctional epithelium of rat or porcine gingiva [12] , [13] , their roles in the junctional epithelium have not been elucidated. Furthermore, microarray and immunohistochemical analyses demonstrated that the expression of claudin-1 in the junctional epithelium following a chronic lipopolysaccharide (LPS) challenge was weaker than that in healthy subjects [14] .…”
Section: Molecular Factors Associated With the Function Of The Junctimentioning
confidence: 90%
“…SYBR green-based real-time PCR was performed as in (Amoozadeh et al, 2015) to evaluate gene expression of Cldn-1, 2, 4, and 7 using GAPDH as the reference standard. Primer pairs designed against the corresponding pig sequences were as follows: Cldn-1: 5 0 -TTCTGGGAGGTGCCCTACTT-3 0 and R: 5 0 -TGGAT AGGGCCTTGGTGTTG-3 0 (Yu et al, 2014); Cldn-2: 5 0 -GCACTG GCATCACCCAGTGT-3 0 and 5 0 -GATGATACAGGCCAACGA GG-3 (Amoozadeh et al, 2015); Cldn-4: 5 0 -CAACTGCGTGG ATGATGAGA-3'and 5 0 -CCAGGGGATTGTAGAAGTCG-3 0 (Pasternak et al, 2015); Cldn-7: 5 0 -TATGAGTTTGGCCCTGC CATC-3'and 5 0 -CCTTGGCAGAATTGGGCTTAG-3 0 (Saitoh et al, 2009) and GAPDH: 5 0 GCAAAGTGGACATGGTCGCC ATCA-3 0 and 5 0 -AGCTTCCCATTCTCAGCCTTGACT-3 0 (Amoozadeh et al, 2015).…”
Section: Rt-pcr For Mrna Analysismentioning
confidence: 99%
“…In oral epithelia, however the existence of TJs was detected by means of ultrathin sections, but the functional significance was doubtful because the frequency of the TJs was quite low [ 23 , 26 , 27 ]. On the other hand, OCD is a reliable marker protein for TJ [ 12 ] and this was observed in oral mucosae, namely the buccal mucosa in dogs [ 1 ] and the gingiva in humans [ 5 , 15 , 18 ], and pigs [ 24 ]. However, the distribution pattern and barrier ability in oral epithelia are still unclear, and no report is available for TJs in the palatal epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…In oral mucosae, OCD, and CLD-1, -4 and -7 have been detected in the buccal epithelium, and the outer and inner epithelia of gingiva in some mammalian species [ 1 , 5 , 9 , 15 , 24 ]. However the combinations of CLD expression patterns vary depending on the types of mucosae and species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation